2013
DOI: 10.2196/jmir.2655
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Online Evaluations on a Physician Rating Website: Evidence From a German Public Reporting Instrument

Abstract: BackgroundPhysician rating websites (PRW) have been gaining in popularity among patients who are seeking a physician. However, little evidence is available on the number, distribution, or trend of evaluations on PRWs. Furthermore, there is no published evidence available that analyzes the characteristics of the patients who provide ratings on PRWs.ObjectiveThe objective of the study was to analyze all physician evaluations that were posted on the German PRW, jameda, in 2012.MethodsData from the German PRW, jam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
108
5
7

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(132 citation statements)
references
References 36 publications
12
108
5
7
Order By: Relevance
“…No consistent trends were observed with these variables in previous studies in different physician and geographic populations. 5,8,11 Written comment analysis on www.Vitals.com and www.RateMDs.com demonstrated that positive comments were more likely to be associated with surgeon-dependent factors whereas negative comments were more likely to be associated with surgeon-independent factors. Chi-square tests were used to evaluate the proportion of comment categories (ie, surgeon-dependent and surgeon-independent factors) as related to comment ratings for surgeons (grouped as 1e2 stars, 3 stars, and 4 stars for www.Vitals.com and 4e5 stars for www.RateMDs.com).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No consistent trends were observed with these variables in previous studies in different physician and geographic populations. 5,8,11 Written comment analysis on www.Vitals.com and www.RateMDs.com demonstrated that positive comments were more likely to be associated with surgeon-dependent factors whereas negative comments were more likely to be associated with surgeon-independent factors. Chi-square tests were used to evaluate the proportion of comment categories (ie, surgeon-dependent and surgeon-independent factors) as related to comment ratings for surgeons (grouped as 1e2 stars, 3 stars, and 4 stars for www.Vitals.com and 4e5 stars for www.RateMDs.com).…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Several studies have attempted to correlate factors associated with higher online patient ratings of individual physicians, such as physician sex, years in practice, medical specialty, insurance status, volume of online patient ratings, geographic region, and academic position. 5,8,11 Lopez et al 12 stated that patient reviews of physicians were affected by office staff, access to care, and convenience.…”
mentioning
confidence: 99%
“…The Kendall coefficient (W) [24][25][26][27][28][29] was used to assess the concordance among to judge the concordance. The significance level is set at 0.05.…”
Section: Task 4: Investigating the Features Of The Kendall Coefficienmentioning
confidence: 99%
“…This phenomenon has received the attention of many researchers, and several studies of the OHC have been conducted focusing on various issues, such as how online physician reviews have been used in different countries [2][3][4][5][6][7]; what are the differences between the traditional and online physician reviews [8]; and whether differences in medical specialty areas affect these reviews [5,9]. Nevertheless, in China, even though the OHC might help consumers look for a good physician, the queues at Chinese hospitals are legendary [10], which means that it is not easy to make an appointment with a physician.…”
Section: Introductionmentioning
confidence: 99%